2007
DOI: 10.1111/j.1600-0447.2006.00933.x
|View full text |Cite
|
Sign up to set email alerts
|

Delay in initial treatment contact after first onset of mental disorders in metropolitan China

Abstract: Failure to receive treatment is a pervasive phenomenon among people with mental disorders in metropolitan China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
0
14
0
2
Order By: Relevance
“…According to the National Comorbidity Survey – Replication, the cumulative lifetime probability of treatment of MDD approaches 90%, but median time from disorder onset to first treatment is 8 years (3). Long lags in first contact for depression treatment have also been reported in Italy (10), Mexico (11) and China (12). …”
mentioning
confidence: 89%
“…According to the National Comorbidity Survey – Replication, the cumulative lifetime probability of treatment of MDD approaches 90%, but median time from disorder onset to first treatment is 8 years (3). Long lags in first contact for depression treatment have also been reported in Italy (10), Mexico (11) and China (12). …”
mentioning
confidence: 89%
“…While the public health aspects of psychiatry are largely neglected in medical education worldwide [7], we have previously reported that the public health impact of depression is more widely known among Australian than Chinese medical students [8]. Other issues related to under-treatment of mental disorders in China include immense population size, inadequacies of the health system including poor mental health expenditure, lack of mental health specialists especially in rural areas, as well as stigma in both the community and among health professionals [9,10]. A lack of medical or personal knowledge of common mental health problems like depression may contribute to negative attitudes and reinforce health services neglect and other discriminatory behaviour [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Thus the vast majority of medical presentations of depression will be to doctors without specific mental health expertise. However, only approximately 8% of people suffering from a mood disorder will make contact with a treatment provider for their condition in China [9]. Thus there will be a growing reliance in China upon non-specialist doctors to achieve early recognition and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…En Estados Unidos se observó que en los pacientes con abuso de alguna droga demoran en promedio 6 años y los que hacían abuso del alcohol 9 años 17 . En China, la demora en hacer contacto con los servicios de salud es de 17 años 32 . Estos lapsos de demora pueden ser mayores o menores en comparación a otros trastornos (Depresión y Ansiedad) y según el lugar de la evaluación 17,26,32 .…”
Section: Discussionunclassified
“…En China, la demora en hacer contacto con los servicios de salud es de 17 años 32 . Estos lapsos de demora pueden ser mayores o menores en comparación a otros trastornos (Depresión y Ansiedad) y según el lugar de la evaluación 17,26,32 . El promedio de demora en la población estudiada es mayor al observado en otros países desarrollados y en vías de desarrollo, sin embargo no llega a ser tan alto como en China.…”
Section: Discussionunclassified